2015
DOI: 10.1039/c4dt03820g
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic platinum(ii) isocyanide complexes: convenient synthetic access, polymorphs, and vapoluminescence

Abstract: A convenient synthetic scheme was developed to access a series of square-planar Pt(II) complexes of the form (TBA)[Pt(CN)3(CNR)] (TBA = tetra-n-butyl ammonium cation, R = CH3, c-C6H11, p-(C2H5)-C6H4). These heteroleptic complexes were characterized by combustion analyses, single-crystal X-ray structure determinations, HRFAB-MS, (1)H NMR, ATR-IR, solution UV-Vis, and solid-state emission spectroscopies. Surprisingly, each of these complexes exhibit low energy room temperature solid-state luminescence in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A typical approach involves the use of chromophores such as Pt(II) and Au(I) complexes. [15][16][17][18][19][20][21][22] These complexes can detect small lattice distortions induced by the adsorption of vapour through highly sensitive electronic transitions involving intermolecular metallophilic interactions. Other promising approaches recently developed involve the use of host-guest interactions between the adsorbing material and vapour molecules [23][24][25][26][27][28] or the use of ligand substitution reactions at metal centres.…”
Section: Introductionmentioning
confidence: 99%
“…A typical approach involves the use of chromophores such as Pt(II) and Au(I) complexes. [15][16][17][18][19][20][21][22] These complexes can detect small lattice distortions induced by the adsorption of vapour through highly sensitive electronic transitions involving intermolecular metallophilic interactions. Other promising approaches recently developed involve the use of host-guest interactions between the adsorbing material and vapour molecules [23][24][25][26][27][28] or the use of ligand substitution reactions at metal centres.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Kuwabara et al 25 reported cationic Pt(II) isonitriles showing different emission colors upon varying counterions and solvents. Pt(II) isonitrile complexes with applications as catalysts, 26 hydrogels, 27 and vapoluminescence 28 have been disclosed as well. However, most reported Pt(II) complexes suffer from low emission yields and short lifetimes due to molecular aggregation.…”
mentioning
confidence: 99%
“…Fig. 3 1) are compared with the most recent methods [5,[11][12][13][14][15][16]. From the results presented in Fig.…”
Section: Extraction Methods Validationmentioning
confidence: 99%